The Silent scream [videorecording] - Nathanson, Bernard N.; American Portrait Films . (Anaheim, Calif. American Portrait Films, 1984)
A first trimester suction abortion seen on an ultrasound screen from the fetus's point of view. Described and explained by the narrator .
Produced and directed by Jack Duane Dabner ; executive producer, Donald S. Smith.
Keywords: Abortion -- United States .; Fetus .